Hubble Space Telescope Observations of Variations in Ganymede's Oxygen Atmosphere and Aurora. Issue 5 (18th May 2018) - Molyneux, P. M.; Nichols, J. D.; Bannister, N. P.; Bunce, E. J.; Clarke, J. T.; Cowley, S. W. H.; Gérard, J.‐C.; Grodent, D.; Milan, S. E.; Paty, C.
Abstract: We present high‐sensitivity Hubble Space Telescope (HST) Cosmic Origins Spectrograph and HST Space Telescope Imaging Spectrograph measurements of atmospheric OI 130.4‐nm and OI] 135.6‐nm emissions at Ganymede, which exhibit significant spatial and temporal variability. These observations represent the first observations of Ganymede using HST Cosmic Origins Spectrograph and of both the leading and trailing hemispheres within a single HST campaign, minimizing the potential influence of long‐term changes in the Jovian plasma sheet or in Ganymede's atmosphere on the comparison of the two hemispheres. The mean disk‐averaged OI] 135.6‐nm/OI 130.4‐nm observed intensity ratio was 2.72 ± 0.57 on the leading hemisphere and 1.42 ± 0.16 on the trailing hemisphere. The observed leading hemisphere ratios are consistent with an O2 atmosphere, but we show that an atomic oxygen component of 10% is required to produce the observed trailing hemisphere ratios. The excess 130.4‐nm emission on the trailing hemisphere relative to that expected for an O2 atmosphere was 11 R. The O column density required to produce this excess is determined based on previous estimates of the electron density and temperature at Ganymede and exceeds the limit for an optically thin atmosphere. The implication that the O atmosphere is optically thick may be investigated in future by observing Ganymede as it moves into eclipse or by determining the ratio of the individual components within the 130.4‐nm triplet. Key Points: Ganymede's FUV oxygen emissions were observed on both orbital leading and trailing hemispheres in the same HST campaign for the first time The observed hemispheric difference in the brightness of both emissions and in their ratio therefore cannot be caused by long‐term changes The OI] 135.6‐nm/OI 130.4‐nm ratio on the trailing hemisphere suggests that an optically thick O atmosphere is present there with O/O2 10%